Schools and Manifestations of Oriental Miniature Art - San’at , Toxirov; Umidullayevna, Sobirova Sharofat (Miasto Przyszłości, 2023)
The article presents Oriental miniature schools and their history, an analysis of the culture of Samarkand and Herat in the Timurid era on the basis of sources. The thought of the processes of development of the Fine Arts and schools of the Timurid and Timurid periods, as well as miniatures made on the manuscripts of the Timurid period.